2021
DOI: 10.24187/ecostat.2021.526d.2051
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Tax and Transfer System – Issues for Income Tax and Other Public Policies

Abstract: In France, married couples or couples in civil partnerships must declare their resources jointly and are allocated two tax units. This tax system, referred to as the marital quotient, represents a financial package of around 10 billion euros. Using the Ines microsimulation model, we simulate three reforms of this system: an individualisation of taxation, a reduction of marital quotient to 1.5 tax units while allowing married couples/couples in civil partnerships to opt for individual taxation and, finally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In line with this thesis, several authors have stressed that singles have more harsh living conditions than married individuals, especially in terms of their economic situation. In both France and in the United States, single individuals often pay a higher income tax than married couples (Alm et al, 2002; Carbonnier, 2021), and a recent study observed a different treatment between the two groups by the US Social Security system (Groneck & Wallenius, 2021). Inequality has also been observed within private enterprises in which being married allows men to earn more than their single peers by simple reputation (Antonovics & Town, 2004).…”
Section: What Is New?mentioning
confidence: 99%
“…In line with this thesis, several authors have stressed that singles have more harsh living conditions than married individuals, especially in terms of their economic situation. In both France and in the United States, single individuals often pay a higher income tax than married couples (Alm et al, 2002; Carbonnier, 2021), and a recent study observed a different treatment between the two groups by the US Social Security system (Groneck & Wallenius, 2021). Inequality has also been observed within private enterprises in which being married allows men to earn more than their single peers by simple reputation (Antonovics & Town, 2004).…”
Section: What Is New?mentioning
confidence: 99%